PARAMETERS OF THE INTERCONDYLAR FOSSA OF THE FEMUR IN CHILDRENIN NORMAL CONDITIONS AND WITH CONGENITAL MALFORMATIONS OF THE LOWER LIMBS - Yakushkin, Yevhenii; Khmyzov, Sergij; Zlatnik, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
According to literature sources, radiography can indirectly visualize congenital insufficiency of the cruciate ligaments both in isolated form and in combination with other congenital malformations of the lower extremities. Objective. To study the parameters of the intercondylar fossa of the femur in children of different age groups with stable/unstable knee jo ints due to congenital malformations of the lower limbs using instrumental imaging methods. Methods. A prospective diagnostic study was conducted of 359 knee joints of 217 children who were treated at the pediatric orthopedics clinic from 2019 to 2022 and with a retrospective control group (2010–2021). limbs, as well as with congenital malformations of the lower limbs. X-ray examinations were performed on the OPERA T90cex X-ray and fluoroscopic system. Results. 217 patients took part in the study, including 105 patients without knee joint pathology and 112 with congenital malformations of the lower limbs. Comparison of the accuracy of radiological diagnostic indicators was performed using the Studentʼs t-test with the results of computer and magnetic resonance imaging studies, which showed the absence of a statistically significant difference in the results research. A diagnostic study was also conducted to find the regularity of the development of the knee joints and to identify the parameters of the radiological norm of the development of the intercondylar fossa of the femur in children of different age categories. Conclusions. Using the results of instrumental studies, the parameters of the intercondylar fossa of the femur in children of different age categories with stable and unstable knee joints due to congenital malformations of the lower limbs were investigated. The results of the study should be taken into account for the diagnosis of congenital defects of the knee joint.